The cultural connect: Mobile phone use and identity - Lloyd, Clare (Watson Ferguson & Company, 2007)
This paper investigates the social implications and cultural constructs related to the use of mobile phones, and it explores how this use interacts with, frames and grounds the user's identity and sense of personal agency. The mobile phone conveys an impression of independence - it delivers a sense of individual freedom, fluidity, and mobility. However our consent to the mobile phone?s constant presence means that we are relentlessly contactable. A mobile phone is both personal and intimate. It offers us intimacy, yet this capacity for intimate communication may also be appropriated by others, making us unwilling objects of the intimate personal communication practices of other people. It can be used as a substitute for absent friends and it can be visually and technically embellished as a tool for self expression. This paper explores how the mobile phone shapes, and is shaped by, our personal experience.